2015
DOI: 10.1002/prep.201400273
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Heat and Kinetics of Nitration of 1,2,4‐Triazol‐5‐one (TO)

Abstract: The heat effects of the nitration and dissolution processes of 1,2,4‐triazol‐5‐one (TO) in acidic environments were measured by differential reaction calorimetry. The kinetics of nitration of TO in a 200‐mL reactor were investigated by UV/Vis spectroscopy. Temperature changes were measured in a 10‐L batch reactor during the TO nitration. A model of kinetics for the synthesis of 3‐nitro‐1,2,4‐triazol‐5‐one (NTO) was proposed and it was used to simulate the phenomena occurring in the calorimeter and in the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…the reaction order of TO is 1. Accordingly,i ti sp roved to be suitable that the reactiono rder of TO is assumed as 1a sp roposed in the literature [1,[10][11][12][13].…”
Section: Verification Of the Empirical Equationsupporting
confidence: 91%
See 2 more Smart Citations
“…the reaction order of TO is 1. Accordingly,i ti sp roved to be suitable that the reactiono rder of TO is assumed as 1a sp roposed in the literature [1,[10][11][12][13].…”
Section: Verification Of the Empirical Equationsupporting
confidence: 91%
“…The kinetic parameters of apparent activation energy [15] and frequency factor for TO nitration are assumed to be constant and independent on the HNO 3 concentration and the reactiono rder was not assumed as 1f or TO in advance, which is different from earlier reports [1,[10][11][12][13].I f the reactionr atesc alculated using the proposede quation are in agreement with the real values determined,i .e. macroscopic phenomena, it suggestst hat constant activation energy and frequency factor are reasonable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar strategy might work for the synthesis of 5-nitrimino-3-nitro-1,2,4-triazole (Scheme 4). When NTO is dissolved in concentrated nitric acid reactive by-products are formed [3,28]. If ANTA is mixed with concentrated nitric acid similar reactions might occur and the proposed route for 5-nitrimino-3-nitro-1,2,4-triazole (Scheme 4) would need to be modified.…”
Section: Synthetic Routesmentioning
confidence: 99%
“…Further research into the nitration of TO was undertaken by Trzciń ski et al [44].T he authors investigated the heat of reactiono fT On itration using ad ifferential reactionc alorimeter. The averageh eat of reaction value for the nitration of TO using various nitration mixtures was determined ( In 1990, Boyer et al reported the synthesis of the insensitive explosive4 ,10-dinitro-2,6,8,12-tetraoxa-4,10-diazaisowurtzitane (TEX), which is synthesizedb yt he base catalyzed formation of 1,4-diformyl-2,3,5,6-tetrahydroxypiperazine (DFTHP)f ollowed by condensation of trimeric glyoxal with DFTHP in acidic solutiona nd subsequentn itration (Scheme 3) [46].…”
mentioning
confidence: 99%